Non-pharmacological Management of Multiple Sclerosis: A Focus on Diet and Supplementation - Górowska, Anna; Lenart, Julia; Janik, Natalia; Wadowska, Zuzanna; Janowiak, Julia; Sobiś, Martyna; Bogacka, Anna; Kiersznowska, Nina; Buchman, Małgorzata; Miłek, Barbara (Quality in Sport, 2025)
Background: Multiple sclerosis (MS) is a chronic autoimmune and demyelinating disease of the central nervous system, characterized by inflammation, neurodegeneration, and diverse neurological symptoms. Emerging evidence suggests that dietary interventions and supplementation may influence disease activity, symptom severity, and overall quality of life in MS patients. Objective: This review aims to present current knowledge on the effects of specific dietary patterns, caloric restriction, and nutritional supplementation on the clinical management and progression of MS. Methods: Peer-reviewed studies published between 2015 and 2025 were identified through PubMed and Google Scholar using keywords including “multiple sclerosis,” “diet,” “ketogenic diet,” “Swank diet,” “Wahls diet,” “fasting,” “vitamin D,” and “epigallocatechin gallate.” Studies were selected based on scientific credibility, relevance, and methodological integrity. Results: Evidence suggests that the Swank and Wahls diets, despite differing approaches, both improve fatigue, mood, and quality of life by emphasizing high fruit and vegetable intake and limiting saturated fats and processed foods. Ketogenic diet enhance mitochondrial function, reduce pro-inflammatory enzyme expression, and may support remyelination. Vitamin D supplementation demonstrates immunomodulatory and neuroprotective effects, while epigallocatechin gallate may further reduce inflammation, anxiety, and cardiovascular risk. However, limitations of these studies include small sample sizes, short study durations, and varies interventions, complicating the isolation of individual effects. Conclusions: Dietary interventions and supplementation represent promising adjunctive strategies for MS management. While current evidence supports potential benefits in symptom reduction, neuroprotection, and quality of life, large-scale, long-term randomized controlled trials are needed to establish efficacy, safety, and underlying mechanisms.